2019
DOI: 10.1177/0361198119837219
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Crash Rates at Freeway Diverge Areas using Bayesian Tobit Modeling Framework

Abstract: The goal of this study is to evaluate the impact of various risk factors on crash rates at freeway diverge areas. Crash rates data for a three-year period from 367 freeway diverge areas were used for analysis. Four candidate Tobit models were developed and compared under the Bayesian framework: a traditional Tobit model; a random parameters Tobit (RP-Tobit) model; a grouped random parameters Tobit (GRP-Tobit) model; and a random intercept Tobit (RI-Tobit). The results showed that the RP-Tobit model performs be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
(129 reference statements)
1
11
0
Order By: Relevance
“…The random parameters multivariate Tobit model was used by Guo et al to evaluate the risk factors on crash rates of different collision types [15]. On the same note, Guo and Sayed a study using Four candidate Tobit models to evaluate the impact of various risk factors on crash rates at freeway diverge areas [16]. By using random parameters multinomial logit regression, Guo et al identified significant factors contributing to the severity of e-bike collisions [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The random parameters multivariate Tobit model was used by Guo et al to evaluate the risk factors on crash rates of different collision types [15]. On the same note, Guo and Sayed a study using Four candidate Tobit models to evaluate the impact of various risk factors on crash rates at freeway diverge areas [16]. By using random parameters multinomial logit regression, Guo et al identified significant factors contributing to the severity of e-bike collisions [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ignoring this inherent variability could lead to incorrect inferences and may lead to a bias in parameter estimates. To address this, researchers have proposed developing random parameter Tobit models to analyze collision rates and to overcome this limitation [30,[35][36][37][38][39][40][41]. More recent studies have also attempted to account for the correlation between collision severities by developing multivariate Tobit models.…”
Section: Methodsmentioning
confidence: 99%
“…e conditional logit model was applied to quantitatively analyse the relative safety performance of SC in different traffic flow states while controlling for the effects of other traffic related variables, such as weather condition, geometric metric design, road pavement, etc. e model can be written as [33][34][35][36][37]…”
Section: Bayesian Conditional Logit Modelmentioning
confidence: 99%